(untitled) (Bangladesh Journal of Pharmacology, 2021)
This study was explored the renoprotective effect of Tongxinluo (a Traditional Chinese Medicine) on diabetic kidney disease and its underlying mechanism. The results revealed significant (p<0.05) up-regulation of the expression of Bcl-2 and down-regulation of NF-κB p-p65, ASC, NLRP3, caspase-1, cleaved GSDMD, IL-1β, caspase-3, Bax and the ratio of Bcl-2 and Bax in immortalized proximal tubular HK-2 cells cultured by hyperglycemia combined with hyperlipidemia. In db/db mice, Tongxinluo treatment substantially decreased the 24 hours albuminuria excretion rate and the urine albumin-creatinine ratios and renal morphologic abnormalities. Similarly, the levels of NF-κB p-p65, NLRP3, caspase-1, cleaved GSDMD, IL-1β, caspase-3, and the ratio of Bcl-2 and Bax were down-regulated by Tongxinluo treatment in the kidney samples of db/db mice (p<0.05). Taken together, according to the anti-pyroptosis and anti-apoptosis effect of Tongxinluo, it shows the potential to be effective for the treatment of diabetic kidney disease.